"I repeat the question porque no me entero": The use of L1 in the didactics of EFL teaching class by pre-service Primary Education teachers - Estrada-Chichón, José L. (2020)
This work analyses the use of Spanish (mother tongue) by pre-service teachers (N=55) during a class activity that consists of explaining and solving Primary Education (6-12) mathematical problems in English (foreign language). The objectives are established in the form of three research questions about the amount of frequency of Spanish; its functional categories according to the original classification of De la Campa and Nassaji (2009); and the lack of competence in English of the participants. This is a mixed-method research since it includes both quantitative and qualitative data, collected through a questionnaire; the recordings of the pre-service teachers’ discourse; and a virtual interview. The novelty of the study lies in a new functional category: lack of foreign language competence, which precedes others such as personal comment, activity instruction, arbitrary code-mixing, and translation, for instance. Likewise, 78.18% used Spanish at least once during the activity, although this is limited to 2.13/person. This works sheds light not only on the low amount of Spanish but especially on its functional categories, revealing a lack of language competence and pedagogical skills among the pre-service teachers. The paper ends with some recommendations for language teachers.